2021
DOI: 10.3389/fmicb.2021.649091
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis Reveals Disturbance of Nanosecond Pulsed Electric Field in the Serum Metabolic Spectrum and Gut Microbiota

Abstract: Nanosecond pulsed electric field (nsPEF) is a novel ablation technique that is based on high-intensity electric voltage to achieve tumour-killing effect in the target region, and increasingly considered for treating tumours of the liver, kidneys and other organs with rich blood supply. This study aims to observe effect of nsPFE treatment on serum metabolites and gut microbiota. The serum and faecal specimens of the pigs were collected pre- and post-treatment. The gut microbiota of pigs was sequenced by Illumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Previous studies have shown ( Yin et al, 2016 ; Qian et al, 2020 ) that nsPEF, as a local treatment, can stimulate a systemic immune activation effect and prevent HCC from metastasizing in the liver and developing in distant areas. There have been microecological studies suggesting that the microecology and metabolism of the digestive tract play an important role in this process ( Dong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown ( Yin et al, 2016 ; Qian et al, 2020 ) that nsPEF, as a local treatment, can stimulate a systemic immune activation effect and prevent HCC from metastasizing in the liver and developing in distant areas. There have been microecological studies suggesting that the microecology and metabolism of the digestive tract play an important role in this process ( Dong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our innovation is to confirm the effectiveness of nsPEFs as a new generation of minimally invasive ablation tools for HCC through gut microbiome and serum metabonomics analysis. In the study by Dong et al, pigs were treated with nsPEFs, and the effects of nsPEFs on serum metabolism and gut microbiome were observed by multiomics analysis ( Dong et al, 2021 ). However, their research focused on the metabolic changes associated with liver injury and the changes in microflora pre- and post-treatment, and there was no animal model of HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation